1999
DOI: 10.1007/s004170050340
|View full text |Cite
|
Sign up to set email alerts
|

Motility and binocularity outcomes in vitrectomy versus scleral buckling in retinal detachment surgery

Abstract: The findings confirm that ocular motility problems are not exclusive to scleral buckling, with the incidence being similar in both groups. Slinging of the extraocular muscles and the accompanying dissection, resulting in the 'fat adherence syndrome', must be considered as contributory factors. The visual deficits which inevitably occur as the result of retinal detachment seem to play a more major role in the disruption of binocularity in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…A total of 48% of our study group comprised of patients who, in contrast to other studies, had undergone PPV detachment repair. Wright et al 11 reported ocular motility problems in a group of PPV patients, where 4 of 17 patients had manifest deviations. In contrast, Fison and Chignell 10 did not find any patients with diplopia after vitrectomy in their series of 125 consecutive cases of vitrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 48% of our study group comprised of patients who, in contrast to other studies, had undergone PPV detachment repair. Wright et al 11 reported ocular motility problems in a group of PPV patients, where 4 of 17 patients had manifest deviations. In contrast, Fison and Chignell 10 did not find any patients with diplopia after vitrectomy in their series of 125 consecutive cases of vitrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conflicting reports show that PPV has either no effect on motility or a similar effect to external buckling. 10,11 We conducted a retrospective study of patients treated for persistent diplopia after RD surgery over a 2-year period to ascertain:…”
Section: Introductionmentioning
confidence: 99%
“…Since strabismus surgery after scleral buckle placement is an uncommon procedure, it was difficult to analyze a large group of patients from a single institution. Indeed, the largest case series in the literature only included 20, 21 17, 22 and 12 26 cases. Our small sample size limited the power of our study.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,11,12 Restrictive fibrosis has been observed during strabismus surgery following retinal cryopexy without the use of any external exoplants. [13][14][15] These multiple etiologies all combine to result in strabismus often seen following vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 Orbital scarring and mass effect of the exoplant are the usual explanations for the development of strabismus, but other potential factors may include local anesthetic toxicity 8 or sensory disturbance. 1 Rates of permanent long-term diplopia following retinal detachment repair vary from 5% to 25%.…”
mentioning
confidence: 99%